Pengaruh Edukasi Melalui Whatsapp Group Terhadap Pengetahuan Remaja Putri Tentang Menstruation Self Care - Asyaul Wasiah; Eka Sarofah Ningsih (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: The majority of young women have some wrong beliefs and habits related to self-care during menstruation. Menstruation is a natural process in the female reproductive cycle, but if it is not managed properly it will result in problems with the reproductive organs such as stomach cramps, itching and an unpleasant odor. Methods: The design in this study was quasi-experimental with pre-test and post-test with control group design. The sample of this study was students of class 7 - 8 Mts Hasyim Asy'ari Kedungmegarih who had menstruated. The total sample is 70 people consisting of 35 control groups and 35 intervention groups. The sampling technique is simple random sampling. Education via WhatsApp is carried out for 2 weeks and material is provided with different discussion topics every day. The posttest is carried out one menstrual period in the next. This research questionnaire uses a Likert scale in the form of a check list. The questionnaire consists of 20 statements regarding menstruation self care. Analysis using Mann-Whitney at α < 5% Results: The results showed that the P value after education via WhatsApp, in the intervention group was 0.000* which meant that there were differences in menstruation self care before and after being given education via WhatsApp while the p value in the control group was 0.004 which meant there were differences in menstruation self care before and after being given education via WhatsApp. The results of the Mann Whitney statistical test showed a p value of 0.000 (p≤α=0.05). It can be concluded that there was an effect of education via WhatsApp on the increase in the average menstruation self care score before and after educational intervention via WhatsApp was carried out for students of class VII and VIII Mts Hasyim Asy'ari. The targeted output is sinta 4 accredited journal Conclusion: Based on the results of research on the effect of education through WhatsApp on menstruation self care in class VII and VIII students of Mts Hasyim Asy'ari, it can be concluded that WhatsApp social media can increase menstruation self care in young women, education through WhatsApp social media is an alternative medium in the delivery process health information about menstruation self care for young women.